mRNA-miRNA networks identify metabolic pathways associated to the anti-tumorigenic effect of thyroid hormone on preneoplastic nodules and hepatocellular carcinoma - Serra, Marina; Pal, Rajesh; Puliga, Elisabetta; Sulas, Pia; Cabras, Lavinia; Cusano, Roberto; Giordano, Silvia; Perra, Andrea; Columbano, Amedeo; Kowalik, Marta Anna (Frontiers in Oncology, 2022)
Background Thyroid hormones (THs) inhibit hepatocellular carcinoma (HCC) through different mechanisms. However, whether microRNAs play a role in the antitumorigenic effect of THs remains unknown. Methods By next generation sequencing (NGS) we performed a comprehensive comparative miRNomic and transcriptomic analysis of rat hepatic preneoplastic lesions exposed or not to a short-term treatment with triiodothyronine (T3). The expression of the most deregulated miRs was also investigated in rat HCCs, and in human hepatoma cell lines, treated or not with T3. Results Among miRs down-regulated in preneoplastic nodules following T3, co-expression networks revealed those targeting thyroid hormone receptor-β (Thrβ) and deiodinase1, and Oxidative Phosphorylation. On the other hand, miRs targeting members of the Nrf2 Oxidative Pathway, Glycolysis, Pentose Phosphate Pathway and Proline biosynthesis – all involved in the metabolic reprogramming displayed by preneoplastic lesions– were up-regulated. Notably, while the expression of most miRs deregulated in preneoplastic lesions was not altered in HCC or in hepatoma cells, miR-182, a miR known to target Dio1 and mitochondrial complexes, was down-deregulated by T3 treatment at all stages of hepatocarcinogenesis and in hepatocarcinoma cell lines. In support to the possible critical role of miR-182 in hepatocarcinogenesis, exogenous expression of this miR significantly impaired the inhibitory effect of T3 on the clonogenic growth capacity of human HCC cells. Conclusions This work identified several miRNAs, so far never associated to T3. In addition, the precise definition of the miRNA-mRNA networks elicited by T3 treatment gained in this study may provide a better understanding of the key regulatory events underlying the inhibitory effect of T3 on HCC development. In this context, T3-induced down-regulation of miR-182 appears as a promising tool.